3(x-1)=3(x+3)

Simple and best practice solution for 3(x-1)=3(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-1)=3(x+3) equation:


Simplifying
3(x + -1) = 3(x + 3)

Reorder the terms:
3(-1 + x) = 3(x + 3)
(-1 * 3 + x * 3) = 3(x + 3)
(-3 + 3x) = 3(x + 3)

Reorder the terms:
-3 + 3x = 3(3 + x)
-3 + 3x = (3 * 3 + x * 3)
-3 + 3x = (9 + 3x)

Add '-3x' to each side of the equation.
-3 + 3x + -3x = 9 + 3x + -3x

Combine like terms: 3x + -3x = 0
-3 + 0 = 9 + 3x + -3x
-3 = 9 + 3x + -3x

Combine like terms: 3x + -3x = 0
-3 = 9 + 0
-3 = 9

Solving
-3 = 9

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 4ax-12bx=40b-b | | 6/50x^4y^3,9/25xy^2 | | 5(n+7)+5=10n-5 | | 62=(3x-5)+3x+(4x+2) | | (2x+1)(ax+b)=6x^2-5x^2+c | | 2(3x-7)=6(5+9)+4 | | -7=1/5x | | 4ax+b=12bx+40b | | 4/5x^2y,8/3xy,12/13xy^5 | | 2(5x-1)=8(x+1) | | 2x^2+3x+j=0 | | 7t^2-112= | | 3y-1=2y-5 | | n=3.64+12 | | 60x^3+24x^2-360x-144= | | 3y+5-7y-7= | | 30x-15x=150 | | -11+x=4 | | 25k^2+81= | | -5/0 | | 4x+12=x+14-12 | | 9r^2+30r+25= | | x^2-64=12x | | 2sin(2x-1)=0 | | 4x+12=x+14 | | 3/5-4/5 | | 21=-3/8× | | x=.6+384 | | 2x+3=5x+97 | | 7=-7/5x-7 | | y=-7/5(-5)-7 | | 64c^2-25t^2= |

Equations solver categories